2022
DOI: 10.1007/s10560-022-00829-5
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Parenting Experiences of Care-Experienced Youth in Ghana and Uganda

Abstract: Although sub-Saharan Africa has the world’s highest rates of early pregnancy, there is little awareness of pregnancy and parenting among young people in out-of-home care in this region. Therefore, this study looked into the experiences of pregnancy and parenting among young women who had been in residential care in Ghana and Uganda. We gathered data from ten parenting care leavers in both countries using semi-structured interviews and then analyzed the data from the interviews thematically. The study’s finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Money is a theme seen often throughout literature as a force behind food insecurity. In similar studies, teenage mothers described the financial constraints that came with motherhood as the greatest barrier to meeting their and their child's nutritional needs [14][15][16][17]. Similar findings have been reported in other studies in Eritrea [18] and the United States [19,20].…”
Section: Barrierssupporting
confidence: 83%
“…Money is a theme seen often throughout literature as a force behind food insecurity. In similar studies, teenage mothers described the financial constraints that came with motherhood as the greatest barrier to meeting their and their child's nutritional needs [14][15][16][17]. Similar findings have been reported in other studies in Eritrea [18] and the United States [19,20].…”
Section: Barrierssupporting
confidence: 83%
“…Studies, including one in the USA, reveal that pregnant adolescents, especially those with unintended pregnancies, often hesitate to disclose their condition due to fear of judgment and discrimination [27]. This trend is consistent across various regions, including Uganda [28], Kenya [29,30], Nigeria [31], Ghana [32], Myanmar [33], and Malaysia [34]. Such stigma has tangible consequences, obstructing access to essential maternal health services like antenatal care and safe delivery options and in uencing critical decisions around pregnancy, sometimes leading to unsafe abortions and increased maternal mortality [35,36].…”
Section: Introductionmentioning
confidence: 93%
“…Relatedly, Frimpong-Manso and colleagues ( 2022 ) examined the experiences of pregnant and parenting young women who had been in residential care in Ghana and Uganda found that access to adequate sexual and reproductive health supports was identified as a key factor for early pregnancy. In both countries, access to continued resources after leaving care is limited, and the authors recruited 10 young mothers who had spent time in residential care and a subsequent transitional program to participate in interviews about their experiences of pregnancy and parenting.…”
mentioning
confidence: 99%